Open Unemployment Rate Based on Age Group and Residence Area using Chi-square Analysis Period 2015-2018 - Putra, Rizaldi; Tanjung, Amries Rusli; Renaldo, Nicholas (Reflection: Education and Pedagogical Insights, 2024)
The purpose of this research is to analyze the relationship between the open unemployment rate (TPT) and demographic factors such as age group and residence area (urban and rural) in Indonesia during the period 2015-2018 using Chi-square analysis. This study employs a quantitative research approach with a descriptive and inferential statistical analysis to examine the relationship between the Open Unemployment Rate (TPT), age group, and residence area (urban vs. rural) in Indonesia from 2015 to 2018. The research uses secondary data obtained from official labor market statistics. Based on the results of the National Labor Force Survey (Sakernas), issued by the Central Statistics Agency (BPS) in 2018, the TPT in urban areas was 6.45 percent while the TPT in rural areas was only 4.04 percent. Compared to 2017, the TPT in urban areas itself decreased by 0.34 percent while the TPT in rural areas increased by 0.03 percent. To build upon this study, future research could explore the role of education and skill mismatches such as investigating how educational attainment and field of study influence employment outcomes could provide a deeper understanding of skill mismatches in the labor market.